2021
DOI: 10.3389/fpls.2021.746517
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytochrome-Interacting Factor Genes in Pepper and Functional Analysis of CaPIF8 in Cold and Salt Stress

Abstract: As a subfamily of basic helix-loop-helix (bHLH) transcription factors, phytochrome-interacting factors (PIFs) participate in regulating light-dependent growth and development of plants. However, limited information is available about PIFs in pepper. In the present study, we identified six pepper PIF genes using bioinformatics-based methods. Phylogenetic analysis revealed that the PIFs from pepper and some other plants could be divided into three distinct groups. Motif analysis revealed the presence of many con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Thus, the adaptability of plants to salt stress was improved. The expression levels of these genes were generally consistent with previous studies [ 54 , 55 ]. These results suggested that plants can not only improve their tolerance to low temperature by combining with cis-acting elements of downstream target genes, but also regulate the expression of downstream genes related to salt stress through ABA-dependent and ABA-independent pathways, as well as ROS and SOS pathways, so as to make plants more adapted to high salt environment.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the adaptability of plants to salt stress was improved. The expression levels of these genes were generally consistent with previous studies [ 54 , 55 ]. These results suggested that plants can not only improve their tolerance to low temperature by combining with cis-acting elements of downstream target genes, but also regulate the expression of downstream genes related to salt stress through ABA-dependent and ABA-independent pathways, as well as ROS and SOS pathways, so as to make plants more adapted to high salt environment.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, PIFs (phytochrome-interacting factors), a subfamily of bHLH TFs, mainly participate in the photomorphogenic development, and several members also as thermo-sensors, involved in cold response ( Jiang et al, 2020 ; Zheng et al, 2020 ). Yang et al (2021) found that six PIF members were existed in pepper, including CaPIF1 , CaPIF3 , CaPIF4 , CaPIF7a , CaPIF7b and CaPIF8 , among them, CaPIF8 was induced under cold stress. Here, a new gene (Newgene_7768) encoding PIF3 was identified and was downregulated under cold stress ( Supplementary Table 14 ), which was consistent with the present results on PIF3 ( Jiang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…The expression of the ABA signal transduction-related gene AtSNRK2.4 , the ABA synthesis gene AtNCED3 and gene PIF1/4 regulating ABA synthesis in MbCBF2 transgenic A. thaliana was further explored. From the analysis results of the expression changes of the downstream genes of six important CBF TFs ( Figure 9 ), AtCAT1 ( A. thaliana , NM_118231.4) [ 50 ], AtP5CS ( A. thaliana , D32138.1) [ 51 ], AtNCED3 ( A. thaliana , NM_112304.3) [ 50 ], AtPIF1 ( A. thaliana , CR457097.1) [ 52 ], AtPIF4 ( A. thaliana , NM_001337007.1) [ 52 ] and AtSnRK2.4 ( A. thaliana , AT1G10940) [ 53 ], it can be seen that in a normal growth environment, the expression of these genes in all A. thaliana strains was almost the same. ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%